Application of single shot free‐breathing fast imaging employing steady state sequence in cardiac magnetic resonance imaging. (3rd March 2014) - Wang, Lidong; Cheng, Liuquan; Fang, Fang; Han, Xiaodong; Liu, Aishi; Ma, Lin; Gao, Peiyi; Niu, Guangming
Summary Objective To investigate the imaging quality of single shot (SS) fast imaging employing steady state (FIESTA) sequence in contrast‐enhanced cardiac magnetic resonance (MR) examination, in comparison with the segmented inversion recovery 2D fast gradient echo (IR FGRE) sequence. Materials and methods Fifty‐two cases with suspected or known heart disease were enrolled in this study, including 24 patients who had enhanced myocardium in myocardial delayed enhancement (MDE). We analyzed the imaging quality of the sequences by measuring the myocardium and blood pool signal‐to‐noise ratios (SNR) and the contrast‐to‐noise ratios (CNR) of blood pool relative to normal myocardium and of enhanced myocardium relative to normal myocardium and compared the new sequences with traditional sequence. Results The scanning time of SS FIESTA was significantly shortened as compared to IR FGRE. The differences in the image quality scores, enhanced myocardium (EM) mass and percentages, SNR(bp), SNR(myo), CNR(myo/bp) and CNR(l/bg) were not statistically significant between SS FIESTA and IR FGRE (P>0·05). However, the difference in CNR(em/myo) was statistically significant between SS FIESTA and IR FGRE (P<0·0001), with CNR(em/myo) of IR FGRE higher than SS FIESTA. Conclusion Single shot FIESTA speeded up the acquisition time, halving it to (27·6 ± 1·8 s) instead of 146 + 13·8 s (IR FGRE), it had higher SNR and CNR, and its image quality did not differ significantly from IR FGRE. The SS FIESTA is more suitable for patients with severely heart diseases or those unable to hold breath. 3D IR FGRE sequence had higher SNR(myo) than the others and it is suitable for displaying the subendocardial scar. However, it has more artefacts and poor imaging quality than IR FGRE.